Pendidikan Karakter Siswa Pondok Pesantren Dalam Upaya Mencegah Radikalisme : LITERATURE RIVIEW - Aba Fahmi Roby; Abdul Muhid (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2022)
Character education in an effort to counteract radicalism among Islamic boarding school students is the reason behind the author to write this literature review article, which is to describe character education for Islamic boarding school students in an effort to prevent radicalism. Character education is important to equip students in Islamic boarding schools in countering radicalism. One of them is character education through Islamic religious learning that has been carried out by Islamic boarding schools. Islamic boarding schools are no doubt to form character. In this study, the data acquisition process used a qualitative method with a literature review approach using a bibliography either from journals, articles or books. The main idea or problem that will be discussed in writing paragraphs in this literature review is character education for Islamic boarding school students in an effort to prevent radicalism.